APLIKASI PENCEGAH PLAGIASI JUDUL TUGAS AKHIR DI AMIK TRI DHARMA PEKANBARU BERBASIS WEB - Suwarti Suwarti (I N F O R M A T I K A, 2021)
AMIK “Tri Dharma Pekanbaru is one of the campuses that are starting to develop, the facilities are starting to be complete but still have quite complex weaknesses in submitting the title of the final project. Especially in looking for titles that are not similar to the previous one. Until now, AMIK Tri Dharma Pekanbaru in submitting student final project titles is still using the system manually, by way of students giving the title of their final project in writing to the study program. So that the title submitted by students is often rejected because of the similarity with the previous title or inefficient. Therefore, the existence of this web-based plagiarism prevention application is one way to make it easier for students to submit final assignment titles. The title of this final project is implemented using the PHP programming language while for database processing using MySQL.